Safety and efficacy of aspirin and indobufen in the treatment of coronary heart disease: a systematic review and meta-analysis - Zhang, Xiaochen; Yan, Qiaoyan; Jiang, Jiao; Luo, Hua; Ren, Yu (Frontiers in Cardiovascular Medicine, 2024)
Purpose: This meta-analysis aimed to compare the safety and efficacy of aspirin and indobufen in patients with coronary heart disease. The primary focus was on the incidence of cardiovascular events, bleeding events, and gastrointestinal reactions. Given the relatively limited research on indobufen, this study utilized aspirin as a control drug and employed meta-analysis to integrate existing clinical studies. The goal was to provide a reference for the clinical use of indobufen and to suggest directions for further largescale, multicenter prospective studies. Methods: This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We conducted a comprehensive search of the PubMed, EMBASE, WOS, and Cochrane Library databases to identify all relevant literature on indobufen. A total of nine trials met the inclusion criteria, encompassing seven randomized controlled trails (RCTs) and two retrospective studies. Categorical variables were analyzed using odds ratio and random effects models. Results: The meta-analysis included nine trials, comprising seven RCTs and two retrospective studies. The pooled results indicated that indobufen significantly reduced the incidence of minor bleeding events, and gastrointestinal discomfort compared to aspirin. However, both drugs had similar effects on the incidence of recurrent angina pectoris, myocardial infarction and mortality due to coronary heart disease. Conclusion: Indobufen was associated with fewer gastrointestinal reactions and a low risk of bleeding, making it a viable option for patients with high-risk factors for bleeding and gastric ulcers. Despite this, indobufen’s short history and limited evidence base compared to aspirin highlight the need for further research. Aspirin remains widely available, cost-effective, and the preferred drug for the primary and secondary prevention of cardiovascular and cerebrovascular diseases. Indobufen or other antiplatelet agents should only be considered when aspirin is not tolerated or contraindicated. Further clinical trials are necessary to determine whether indobufen can replace aspirin.